Addressing Workplaces Burnout - Ismail, Fadillah; Nesreen Ibrahim Owaida2, (Advances in Humanities and Contemporary Studies, 2023)
Burnout is a syndrome conceptualized as resulting from chronic workplace stress that has not been successfully managed. Burnout can affect someone’s mental health and it can cause depression if they do not seek professional help. There are a lot of factors that can lead someone to burnout, especially in the workplace. Heavy workload, negative work environment, and lack of social support are the main factors that cause burnout. However, this problem can be prevented by the manager or the company. The ways to reduce burnout at the workplace are by creating a manageable workload, creating a fun and positive work environment, and encouraging social support. This action will create a new environment for the employees. Furthermore, the employees themselves should know how to control themselves. The employee also can try to connect with nature, try to identify their stressor, and get enough sleep. Burnout at the workplace can be prevented if the employer takes care of the employees' welfare